The reality of kinship ties in light of housing policies: A study of the effect of residential spatial distance on kinship ties on a sample of AADL neighborhoods in the cities of Batna and Ain Touta - Akkari, Yacine; Guendouz, Mounir (Journal of Architecture and environment of child, 2024)
The housing policies adopted by the state, especially housing in the form of rent-sale AADL, resulted in a spatial divergence between the subscribers and their relatives group. - For housing, which has become a haven for a large segment of Algerian society, and the study aimed to identify the impact of the spatial dimension of housing on the process of the traditional kinship pattern among the residents of these neighbourhoods, and the availability of social alternatives that can meet their needs outside the limits of kinship relations. Using the descriptive approach and the questionnaire as a tool for data collection, the study showed that there is a decline in the levels of interaction between subscribers and members of the group of relatives, where the matter has become limited to occasional visits and holidays, and that subscribers with rural origins are more attached to their relatives despite the geographical distance, as the study revealed in another aspect. However, social alternatives do not perform the socio-economic functions of the kinship system, and do not provide social and emotional support for individuals in light of spatial distancing.